Impact of Investment, Funding, and Dividend Policies on Food & Beverage Firms' Valuation: IDX 2018-2021: Dampak Kebijakan Investasi, Pendanaan, dan Dividen terhadap Penilaian Perusahaan Makanan & Minuman: BEI 2018-2021 - Mahmudah, Siti Miftakhurrohmah; Setiyono, Wisnu Panggah (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the impact of investment decisions, funding choices, and dividend policies on firm value in the Food and Beverage sector. Analyzing data from 14 IDX-listed companies over 2018-2021, findings indicate significant positive effects of investment and funding decisions on firm value, while dividend policy's influence is negative and insignificant. Together, these factors explain 75.3% of firm value variation, highlighting the pivotal role of strategic financial decisions in shaping company worth and suggesting managerial implications. Highlight : Strategic Financial Decisions: Investment and funding choices significantly impact firm value. Dividend Policy: Despite being insignificant, dividend policy's effect on firm value is negative. Sector-specific Analysis: Findings offer insights into financial dynamics within the Food and Beverage industry. Keywords: Investment, Funding, Dividend Policy, Firm Value, Food & Beverage